Numerical study of convective heat transfer between two parallel vertical flat plates - 391706 Mohd. Khairul Nizam Sharip (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Engineering (Mechanical)) - Universiti Teknologi Malaysia, 2004